Overview of age constraints for gold mineralization in central and western Newfoundland and new 40Ar/39Ar ages for muscovite from selected auriferous zones - Sandeman, Hamish A.I.; Honsberger, Ian W.; Camacho, Alfredo (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2022)
This contribution presents new 40Ar/39Ar laser step-heating data for muscovite associated with four significant orogenic gold-mineralized zones in central and western Newfoundland to build upon existing geochronological constraints for orogenic gold mineralization across much of the Newfoundland Appalachians. Additionally, we provide the first 40Ar/39Ar laser step-heating data for detrital muscovite from gold-mineralized sandstone of the Wigwam Formation (Botwood Group) at the Moosehead gold prospect. Most known gold zones on the isIand occur in proximity to reactivated crustal-scale faults and related structures, and are commonly localized within competent, rigid lithological units (e.g., granitoid rocks); although, some vein systems cut less competent, clastic sedimentary rock sequences. Host rocks range in age from Neoproterozoic to Devonian and may extend into the Carboniferous. Robust Pragian to Emsian (ca. 410–375 Ma) rutile, muscovite and zircon ages constrain the timing of gold mineralization in parts of the Exploits Subzone, whereas less precise age estimates for gold mineralization in the Notre Dame Subzone and Laurentian margin range from Wenlock to Emsian (ca. 433–375 Ma). Collectively, the geochronological data suggest that fluid-pressure cycling associated with gold mineralization in central and western Newfoundland occurred during progressive Siluro-Devonian tectonics associated with the waning stages of the Salinic orogenic cycle and spanning the Acadian and Neoacadian orogenic cycles. Multiple, polyphase, overlapping orogenic events allowed for repeated, gold mineralizing fluid flow events, particularly in proximity to long-lived, reactivated crustal-scale fault zones.